2BIC: taking your adventuring gear to organise pop‐up health information literacy sessions. (30th August 2018) - Vandendriessche, Thomas; Michels, Marleen; Stoop, Linda; Vissenaekens, Natasja; Discart, Inge
Abstract: Academic libraries play an important role in the provision of health information literacy (IL) skills and there are many approaches to how these can be delivered. In this paper, guest writers Inge Discart and colleagues from KU Leuven Libraries 2Bergen Information Centre (2BIC) in Belgium discuss a pop‐up information literacy skills project. In particular, the article presents the findings from an initial information skills needs assessment conducted at the University, followed by how the concept of the pop‐up sessions was developed and promoted throughout the organisation. The paper identifies the variety of sessions offered and the format in which they were delivered, with final results on how these were received and which sessions were the most popular. This article provides insight into an alternative approach to health information skills delivery and the outcomes from it. H S